M MANAJEMEN BARBERSHOP DI PP MADRASATUL QUR’AN TEBUIRENG JOMBANG TERHADAP TINGKAT KEPUASAN KONSUMEN MENURUT EKONOMI SYARI’AH: BARBERSHOP MANAGEMENT AT PP MADRASATUL QUR'AN TEBUIRENG JOMBANG ON THE LEVEL OF CONSUMER SATISFACTION ACCORDING TO SYARI'AH ECONOMICS - Syamsul Feriyanto; Azizah, Ninik (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
Barber services include hair washing, shaving, head massage, and the barbershop's proprietary hairdressing or styling procedures, which are obviously not available in regular barbershops. Madrasatul Qur'an Tebuireng Islamic Boarding School is one of the places where there is currently a hairdressing salon. By using a sharia economic legal framework, this study approach seeks to understand the management of PP MQ barbershops. Information collected from research targets, also called informants or respondents, is used in the field research carried out. Data was collected from visitors and waiters at the barbershop. Conclusions drawn from this research include (First). PP MQ barbershop services are managed using a consistent sharia economic management role model using the ta'awun concept